THE ANXIETY OF PERIMENOPAUSE WOMEN IN FACING MENOPAUSE - Meilita Enggune; Elizabeth Purba; Stilly Nathalia Kakumboti (Journal of Maternity Care and Reproductive Health, 2019)
Anxiety is an unclear feeling, uncertain, and but is not dangerous. In adults, anxiety is caused by things that threaten their self-concept. For example, women who are facing menopause, they may be anxious due to a decline in reproductive function, so they need social support to prevent anxiety. The purpose of this study was to determine the anxiety level of perimenopausal women in facing menopause. The research method used was descriptive research design with a sample of 105 people. The results showed that 36.19% of perimenopausal women experienced mild anxiety levels, 57.14% experienced moderate anxiety levels, 5.71% experienced severe anxiety levels, and 0.96% of perimenopausal women experienced severe panic anxiety levels. It can be concluded that there are women who experience anxiety in facing menopause. Family support, especially husbands, is needed to set daily food diets such as carbohydrates, reduce protein consumption, reduce consumption of fatty foods, high fiber, vitamin C, and calcium, and exercise to reduce complaints related to menopausal symptoms.Keywords: Anxiety, Menopause, Perimenopause.